MÉTODOS NUMÉRICOS RUNGE-KUTTA Y ADAMS BASHFORTH-MOULTON EN MATHEMATICA - Jaime Segarra (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2020)
In this research, the main objective is to study the Runge -Kutta and Adams Bashforth- Moulton numerical methods. Tofulfill the purpose of this study, the Systems of differential equations of the Lotka-Volterra model was used and themathematical software Wolfram Mathematica was used. In the results, the RK4, AB4 and AM4 methods are comparedwith the NDSolve command using the Lotka-Volterra model. The results obtained in the phase diagrams and the table ofpoints of the iteration indicated that the RK4 method has higher precision than the AB4 and AM4 methods.